SYNTHESIS, QUALITY CONTROL AND BIODISTRIBUTION OF TECHNEIUM-99M TRIAMCINOLONE ACETONIDE (99mTc-TA) COMPLEX: AN INFLAMMATION TRACER AGENT - Askari Rizvi, Faheem; Raza Naqvi, Syed Ali; Mehdi, Muhammad; Roohi, Samina; Fawad Zahoor, Ameer; Khan, Zulfiqar Ali; Sohaib, Muhammad; Rasheed, Rashid (Journal of the Chilean Chemical Society, 2017)
In present study synthesis of 99mTc-triamcinolone acetonide (99mTc-TA) complex and its stability using set of quality control parameters such as ligand concentration, reducing agent concentration, pH, temperature and reaction time was assessed. 99mTc-TA complex was characterized in terms of percent (%) yield, stability in saline and serum using chromatographic procedures. Radiochemically the 99mTc-TA complex was found quite stable in saline and serum. After 30 min of reaction the complex showed maximum radiochemical yield of 96.32% which decreased to 96.25 % after 4 h incubation period. In serum, the % yield of radiochemical was remained same up to 2 h which decreased to 93.5% at 24 h time point. Normal biodistribution pattern in Sprague-Dawley rats revealed liver, stomach and kidneys as areas of high 99mTc-TA complex uptake (8.44 ± 1.32, 8.75 ± 1.03 and 12.67 ± 1.21%, respectively) at 1 h post injection time point. Scintigraphy of 99mTc-TA in rabbits showed similar eco as observed in biodistribution study. Based on the promising results obtained in context of in vitro and in vivo stability and biodistribution, 99mTc-TA complex could be further studied to identify the inflammation based diseases.